2000
DOI: 10.1006/mthe.2000.0205
|View full text |Cite
|
Sign up to set email alerts
|

A Targetable, Injectable Adenoviral Vector for Selective Gene Delivery to Pulmonary Endothelium in Vivo

Abstract: Adenoviral (Ad) vectors are promising gene therapy vehicles due to their in vivo stability and efficiency, but their potential utility is compromised by their restricted tropism. Targeting strategies have been devised to improve the efficacy of these agents, but specific targeting following in vivo systemic administration of vector has not previously been demonstrated. The distinct aim of the current study was to determine whether an Ad-targeting strategy could maintain fidelity upon systemic vascular administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
131
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(137 citation statements)
references
References 47 publications
6
131
0
Order By: Relevance
“…We are currently working on gene delivery vectors based on adenoviruses that express iCaspase-9 under the control of an endothelial cell specific promoter, [30][31][32] and that are retargeted to the endothelium by the use of an endothelial-specific ligand incorporated into the viral genome. [33][34][35][36] The aim of this work is to characterize an adenoviral vector that will allow for the delivery of iCaspase-9 specifically to neovascular endothelial cells. The data presented here provide the evidence that justifies the search for such a vector, since it demonstrates unequivocally that once iCaspase-9 is expressed in neovascular endothelial cells, its activation by a cell-permeable dimerizer drug results in disruption of microvessels and a profound reduction in tissue microvascular density in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…We are currently working on gene delivery vectors based on adenoviruses that express iCaspase-9 under the control of an endothelial cell specific promoter, [30][31][32] and that are retargeted to the endothelium by the use of an endothelial-specific ligand incorporated into the viral genome. [33][34][35][36] The aim of this work is to characterize an adenoviral vector that will allow for the delivery of iCaspase-9 specifically to neovascular endothelial cells. The data presented here provide the evidence that justifies the search for such a vector, since it demonstrates unequivocally that once iCaspase-9 is expressed in neovascular endothelial cells, its activation by a cell-permeable dimerizer drug results in disruption of microvessels and a profound reduction in tissue microvascular density in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Refinement and optimization of viral vectors will enhance the suitability of gene therapy for the treatment of a variety of diseases. For target cell types that are relatively refractory to viral vectors, a number of strategies to improve transduction have been reported, and include use of vectors based on alternate serotypes, 1,2 use of bispecific antibodies 3,4 and use of phage display-derived targeting peptides (reviewed in Nicklin and Baker 5 ). Previous studies, using both adenoviruses (Ad) 6,7 and adeno-associated viruses (AAV), 8 have demonstrated the ability of the cyclic RGD-4C peptide 9 to retarget vector tropism through av integrins, leading to enhanced gene delivery to a repertoire of cell types.…”
mentioning
confidence: 99%
“…52 Other Fab-ligand conjugates targeted against Ep-CAM, Tag-72, epidermal growth factor (EGF) receptor, CD-40 and other cell markers have been employed in a similar manner with promising results. 1,[53][54][55][56][57][58] Dmitriev et al 60 developed an elegant alternative to the chemical conjugate approach by creating a single recombinant fusion molecule formed by a truncated, soluble form of CAR (sCAR) fused to either an anti-CD40 antibody 59 or epidermal growth factor (EGF). Using the latter, a nine-fold increase in reporter gene expression was achieved in several EGFR-overexpressing cancer cell lines compared to untargeted Ad or EGFR-negative cells in vitro.…”
Section: Adapter-based Ad Targetingmentioning
confidence: 99%
“…In this regard, Reynolds et al 56 employed a novel bispecific adapter composed of an anti-knob Fab chemically conjugated to a monoclonal antibody (9B9) raised against angiotensin-converting enzyme (ACE), a surface molecule expressed preferentially on pulmonary capillary endothelium and upregulated in various disease states of the lung. Following peripheral intravenous injection of the Ad/Fab-9B9 complex, reporter transgene expression and viral DNA in the lung were increased 20-fold over untargeted Ad.…”
Section: Adapter-based Ad Targetingmentioning
confidence: 99%